RANCANGAN SISTEM ELEKTRONIK KANBAN UNTUK MENINGKATKAN EFEKTIVITAS PRODUKSI JUST IN TIME - ZAHIDI PUTRA PUAR; M TIRTANA SIREGAR (Politeknik APP Jakarta, 2017)
This research describes an electronic Kanban system development in order to replace conventional Kanban system. Many previous research conducted to optimize number of Kanban, however weaknesses still find when there is a change condition of production planning, therefore it must be re-optimization number of Kanban and it will takes time and costs. In current condition, the Company has implemented a manual Kanban system to support their Just In Time production system, but unfortunately it still find problems during implementation due to the system implemented using paper and manual recording. In this research, the electronic Kanban system (e-Kanban) is develop based on computer vision which combined with production systems condition in currently. E-Kanban system is a method to replace manual Kanban irregularity. Based on result through a scenario Master Production Schedule (MPS), Electronic Kanban system can deliver information effciently and effectively with improve 54% compared with conventional systems and 32% compared with manual Kanban.